PENGUASAAN TENTANG KETERAMPILAN METAKOGNISI GURU BIOLOGI SMA DI JEMBER - Suratno, (Jurnal Penelitian Pendidikan Matematika dan Sains, 2009)
Abstrak: The research has been conducted the understanding of metacognitive skill senior high school biology teachers in Jember. Data collecting by using quesioner on June-August 2008, which consist of 80 biology teachers in Jember from 39 senior high school. Questioners which have been validated by experts (judgment experts) were employed as instruments of the research. The data analized by using quantitative descriptive support by Exel for Windows programm. The results of the research, the understanding of biology teachers about metacognition skills Senior high school biology teachers in Jember was very low. Senior high school biology teachers in Jember have not utilized the components of metacogniton skills for biology teaching-learning.